ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP GOOD CORPORATE GOVERNANCE SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Indawati, Indawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This research aims to know the influence of financial performance of Return On Assests (ROA),  Net Profit Margin (NPM), and  Current Ratio (CR) to  Good Corporate Governance (GCG) and the influence of  Good Corporate Governance (GCG) on company value Price To Book Value (PBV). To simplify the research, the authors use the financial statement from period 2010 to 2015. The method of analysis which used in this research is Panel Data analysis method. From the results of research using EVIEWS 9 (Computer Applicaitions tools) based on ?t? test i.e ROA influence and significantly on GCG, NPM negative influence and significantly GCG, CR influence and significantly to GCG, PBV  influence and significantly GCG, and testing based on ?F? test (simultaneous) influence of financial performance  ROA, NPM, CR on GCG the financial performance influence simultaneously on GCG, and influence GCG on PBV based on ?F? test (simultaneous)  GCG has no influence simultaneously on company value PBV. So it can be clonclusion based on ?t? test and ?F? test are done with ROA, NPM, CR and GCG influence and significantly on the company value